The Global Compact Selected Experiences and Reflections - Kell, Georg (Journal of business ethics, 2005)
In this paper, the Executive Head of the Global Compact shares some of his own reflections on the evolution of the Global Compact initiative – United Nations Secretary-General Kofi Annan’s voluntary corporate citizenship initiative in the area of human rights, labor, the environment and anti-corruption. Two main themes are addressed. The first considers the Global Compact’s institutional context, examining how such an initiative is even possible in the historically hierarchical and traditionally business-unfriendly UN. The second concerns the voluntary nature of the initiative and how it interacts with regulatory approaches. It explains what the Global Compact has to offer as a voluntary initiative, as well as how it can make a unique and complementary contribution to regulation-backed initiatives. The paper concludes with a brief consideration of what the future holds for the Global Compact.